2021
DOI: 10.1021/acs.jafc.1c00273
|View full text |Cite
|
Sign up to set email alerts
|

Host Metabolic Disorders Induced by Alterations in Intestinal Flora under Dietary Pesticide Exposure

Abstract: A dietary pesticide residue causes underestimated influences on body health. In this work, experimental mice were exposed to commonly used pesticides that cause insulin resistance, inflammation, and non-alcoholic fatty liver diseases. Alterations in intestinal flora were detected in the exposure groups. The abundance of the flora causing high endotoxin production was intensively increased and led to body inflammation. High Firmicutes/Bacteroidetes and obesity-related flora characteristics were also found. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
(94 reference statements)
0
18
0
Order By: Relevance
“…Alterations of gut microbiota associated with obesity, hyperlipidemia, hepatic lipid accumulation and liver injury has bee also demonstrated, in mice, after exposure to polychlorinated biphenyl 77 (PCB77) 176 . Finally, emerging evidence shows pathogenic relationships between gut dysbiosis, liver toxicity and exposure to other widely diffused contaminants as perfluorooctanoic acid (PFOA), 177,178 and dietary pesticide residues 179 …”
Section: Environmental Factors Gut Microbiota and Nafldmentioning
confidence: 98%
See 2 more Smart Citations
“…Alterations of gut microbiota associated with obesity, hyperlipidemia, hepatic lipid accumulation and liver injury has bee also demonstrated, in mice, after exposure to polychlorinated biphenyl 77 (PCB77) 176 . Finally, emerging evidence shows pathogenic relationships between gut dysbiosis, liver toxicity and exposure to other widely diffused contaminants as perfluorooctanoic acid (PFOA), 177,178 and dietary pesticide residues 179 …”
Section: Environmental Factors Gut Microbiota and Nafldmentioning
confidence: 98%
“…T A B L E 7 External agents potentially able to alter gut microbiota and to promote the onset of NAFLD Dietary nutrients -Saturated fats 138 -Sugars 139,147,159 -Protein malnutrition 213 -Reduced fibre intake 140 Alcohol intake 165 Increased dietary iron 166,167 Toxic chemicals -Cadmium 168,169 -Bisphenol A 171 -Phenanthrene 172 -Triclosan 173 -Polychlorinated biphenyls (PCBs) 175,176 -Perfluorooctanoic acid (PFOA) 177,178 -Pesticides 179 Metformin administration in C57Bl/6J mice fed fatfructose-and cholesterol-rich diet showed protective effects acting on both gut microbiota and integrity of the intestinal barrier. 189 In the ob/ob mice fed a high fat diet, the antidiabetic drug liraglutide modified the relative abundance the composition of gut microbiota phylotypes involved in the pathogenesis of NAFLD via reduced Proteobacteria and increased Akkermansia muciniphilai, and decreased the intra-hepatic fat accumulation, reversing steatosis.…”
Section: Microbiota As a Potential Therapeutic Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…3_Formyl_6_hydroxyindole was negatively correlated with Muribaculaceae . Indole is the precursor of indoxyl sulfate, which linked with cancer, host metabolic disorders, cardiovascular disease, type 2 diabetes, hypertension, and induced intestinal barrier dysfunction [ 42 , 43 , 44 , 45 , 46 , 47 ]. It was reported that dietary supplements of beneficial substances effectively decreased indole-derived metabolites in the host [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…More than 100 trillion microbiotas are harbored in the gastrointestinal tract, which has been compared to the “invisible organ” that is essential to the human body, and plays key roles in human physiology and metabolism such as digestion and nutrition, regulation of immunity, and inflammation and oxidative stress ( Zhou B. et al, 2020 ). Meanwhile, intestinal dysbacteriosis might cause a variety of diseases, such as obesity, metabolic disorders, and inflammatory bowel disease, even cancer ( Gao et al, 2018 ; Khan et al, 2019 ; Zhou X. et al, 2020 ; Liu et al, 2021 ). It is well known that intestinal tract and intestinal flora are always affected by most DBPs in drinking water through oral ingestion.…”
Section: Introductionmentioning
confidence: 99%